(Invited) Pixel-Parallel CMOS Image Sensors with 16-Bit A/D Converters Developed by 3-D Integration of SOI Layers with Au/SiO2 Hybrid Bonding. (25th April 2016) - Goto, Masahide; Hagiwara, Kei; Honda, Yuki; Nanba, Masakazu; Iguchi, Yoshinori; Saraya, Takuya; Kobayashi, Masaharu; Higurashi, Eiji; Toshiyoshi, Hiroshi; Hiramoto, Toshiro
Abstract : We have developed pixel-parallel CMOS image sensors with 16-bit A/D converters (ADCs) by 3-D integration of silicon-on-insulator (SOI) layers. Hybrid bonding of Au electrodes embedded in a SiO2 surface is suitable for a high-density interconnection to deliver pixel-parallel operation of the sensor. Photodiodes, ADCs, and counters are prepared on two SOI layers, and they are connected in each pixel to develop the 128 × 96 pixel-parallel sensors. We have demonstrated successful operation of video imaging with 16-bit digital output and a wide dynamic range of 96 dB, showing the feasibility of high performance 3-D integrated devices.